Dentinogenic ghost cell tumor—a rare case report with review of literature - Agrawal, Yash; Naidu, Giridhar S.; Makkad, Ramanpal Singh; Nagi, Ravleen; Jain, Supreet; Gadewar, Dilip R.; Kataria, Raman (Quantitative Imaging in Medicine and Surgery, 2017)
Dentinogenic ghost cell tumors (DGCT) are very rare tumors considered as solid variants of calcifying epithelial odontogenic cysts (CEOC). They are locally invasive neoplasms and their main characteristic features are ameloblastoma like odontogenic epithelial proliferation, an aberrant keratinization in the form of ghost cells and dysplastic dentin. DGCT occur as two forms intraosseous (central) and extra osseous (peripheral), of which more aggressive intraosseous variety requires careful monitoring and aggressive local resection to prevent recurrence. This paper discusses a case of a 14-year-old male patient with a complaint of swelling in his right mandibular premolar molar region since 4 months and missing permanent right mandibular canine and first premolar was also observed. The lesion was diagnosed with radiological, cytological and histopathological investigations which revealed it to be rarest entity.